Enzymatic Activity, Sensitivity to Antifungal Drugs and Baccharis dracunculifolia Essential Oil by Candida Strains Isolated from the Oral Cavities of Breastfeeding Infants and in Their Mothers' Mouths and Nipples - Pereira, Cristiane Aparecida [UNESP]; Borges Pereira da Costa, Anna Carolina [UNESP]; Silva Machado, Ana Karina [UNESP]; Beltrame Junior, Miltom; Amorin Costa Zoellner, Maria Stella; Junqueira, Juliana Campos [UNESP]; Cardoso Jorge, Antonio Olavo [UNESP] (Springer, 2011)
Candida strains can cause oral candidosis, as well as nipples candidosis and lead to premature weaning or yeast transmission. The aim of this study was to evaluate 51 Candida isolates obtained from the oral cavities of infants during breastfeeding and mothers' oral cavities and nipples, their enzymatic activity and their sensitivity to amphotericin B, fluconazole and Baccharis dracunculifolia essential oil. Among the studied strains, 96.1% produced phospholipase and 78.4% produced proteinase. The antifungal resistance was only observed among isolates of C. albicans, for which three strains showed a resistant activity to fluconazole and one showed a resistant activity to amphotericin B. All strains were sensitive to B. dracunculifolia essential oil with MIC between 0.2 and 6.25 mg/ml. It was concluded that most of the strains showed significant enzymatic activity and were sensitive to amphotericin B and fluconazole. B. dracunculifolia essential oil inhibited the growth of all strains, including the ones resistant to commercial antifungal agents.
Keywords: Candida; Amphotericin B; Fluconazole; Baccharis dracunculifolia; Phospholipase; Proteinase